A prediction model of the surface topography due to the unbalance of the spindle system in ultra-precision fly-cutting machining. (January 2018) - Chen, Dongju; Cui, Xianxian; Pan, Ri; Fan, Jinwei; An, Chenhui
In ultra-precision fly-cutting machining, the aerostatic spindle is the key component, which has significant influence on the machined surface quality. The unbalanced spindle directly affects the machining accuracy. In this article, a prediction model of machining surface topography is proposed which involves the effect of the gas film performance of spindle in microscale. With the Weierstrass function, unstable transient response of the aerostatic spindle system is derived by the motion model of the spindle, which response signal represents the surface profile in the ultra-precision machining. Meanwhile, the experiment is performed with different rotation speed of the spindle. And the effect of the unbalanced aerostatic spindle on the surface generation is discussed in time and frequency domain. The conclusion shows that the similar cyclical surface ripple of the workpiece is independent of the spindle speed, and the rotation speed of the spindle and unbalanced spindle directly affects the machining surface topography. This study is quite meaningful for deeply understanding the influence rule of spindle unbalanced error from the viewpoint of machined surface and vibration frequency.